Analisis Jenis Struktur Rumah Tinggal Di Nias - Waraslin Zebua; Charsa Alim Lase; Elrica Fajariang Mendrofa; Dermawan Zebua (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the types and structural systems of traditional residential houses in Nias and to understand their characteristics, functions, and cultural values. The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation conducted in several traditional villages on Nias Island. The results show that traditional houses in Nias are generally classified into two main types, namely Omo Hada and Omo Sebua, which differ in terms of size, structural complexity, and social function. The structural system utilizes a stilt-house construction with wood as the primary material and joinery techniques without nails, providing high flexibility against dynamic loads such as earthquakes. Furthermore, the use of local materials such as hardwood and thatched leaves reflects local wisdom in sustainable construction practices. However, modernization and changes in community lifestyles have led to a decline in the number of authentic traditional houses. Therefore, preservation efforts are needed through an integrative approach that combines traditional values with modern technology to ensure the sustainability of residential architecture in Nias.